Development of an Allele-Specific PCR Assay for Simultaneous Sero-Typing of Avian Pathogenic Escherichia coli Predominant O1, O2, O18 and O78 Strains - Wang, Shaohui (Public Library of Science, 2014)
Systemic infections by avian pathogenic Escherichia coli (APEC) are economically devastating to poultry industries worldwide. E. coli strains belonging to serotypes O1, O2, O18 and O78 are preferentially associated with avian colibacillosis. The rfb gene cluster controlling O antigen synthesis is usually various among different E. coli serotypes. In present study, the rfb gene clusters of E. coli serotypes O1, O2, O18 and O78 were characterized and compared. Based on the serotype-specific genes in rfb gene cluster, an allele-specific polymerase chain reaction (PCR) assay was developed. This PCR assay was highly specific and reliable for sero-typing of APEC O1, O2, O18 and O78 strains. The sensitivity of the assay was determined as 10 pg DNA or 10 colony forming units (CFUs) bacteria for serotypes O2 and O18 strains, and 500 pg DNA or 1,000 CFUs bacteria for serotypes O1 and O78 strains. Using this PCR system, APEC isolates and the infected tissue samples were categorized successfully. Furthermore, it was able to differentiate the serotypes for the samples with multi-agglutination in the traditional serum agglutination assay. Therefore, the allele-specific PCR is more simple, rapid and accurate assay for APEC diagnosis, epidemiologic study and vaccine development.